Markers of vitality in ovaries of transmen after long-term androgen treatment: a prospective cohort study - Julian Marschalek; Detlef Pietrowski; Sabine Dekan; Marie-Louise Marschalek; Maximilian Brandstetter; Johannes Ott (BMC, 2020)
Abstract Background Gender-affirming hormone therapy has been hypothesized to reduce the patient's reproductive potential in transmen, although the exact long-term effects on future fertility are unknown. Methods In this prospective cohort study we aimed to evaluate ovaries of 20 transmen by using hormone serum levels, histomorphological analysis and fluorescence activated cells sorting (FACS) analysis - in order to assess the amount of vital cells. Results The median total number of follicles per field of view was 39 (IQR 12-122). Of all follicles (n = 1661), the vast majority was primordial (n = 1505, 90.6%), followed by primary (n = 76, 4.6%), abnormal (n = 63, 3.8%) and secondary follicles (n = 17, 1.0%). FACS analysis was available for 13 samples (65.0%) and the median frequency of vital cells was 87.5% (IQR, 77.7-95.4%). Both a higher age (p = 0.032) and a lower BMI (p = 0.003) were significantly associated with a higher frequency of vital cells. Conclusion The majority of ovarian cells after long-term androgen treatment were vital in FACS analysis and histomorphological evaluation revealed a normal cortical follicle distribution. These results are currently exploratory, but might be promising for issues on fertility preservation. Trial registration The study was approved by the ethics committee of the Medical University of Vienna (EK 2240/2016) and was retrospectively registered in the Current Controlled Trials Register (registration number NCT03649087 , date of registration: 28.08.2018).